Theoretical calculations of the structure and UV–vis absorption spectra of hydrated C60 fullerene - Rivelino, Roberto (2006)
A combined Monte Carlo simulation with semiempirical quantum mechanics calculations has been performed to investigate the structure of hydrated fullerene (C60HyFn) and the influence of hydration on its UV–vis spectra. The statistical information of the C60 fullerene aqueous solution (C60FAS) is obtained from NPT ensemble including one C60 fullerene immerses in 898 water molecules. To obtain an efficient ensemble average, the auto-correlation function of the energy has been calculated. The analyzed center-of-mass pair-wise radial distribution function indicates that, on average, there are 65 and 151 water molecules around the first and second hydration shells, respectively, of a single C60 molecule. To calculate the average UV–vis transition energies of C60HyFn, only the statistically uncorrelated configurations are used in the quantum mechanical calculations (INDO/CIS). These involve hundreds of supramolecular structures containing one C60 fullerene surrounded by the first hydration shell. The calculated average transitions at 268 and 350 nm are in very good agreement with the experimental prediction.